The role of oxygen in the functioning of the Earth system: past, present and future - Stankowski, Wojciech (Geologos, 2023)
In the Solar System, the coming into existence of a peculiar, fully developed atmosphere on Earth was determined by the ‘Great Oxidation Event’ at the turn of the Proterozoic and Palaeozoic. Within about 600 million years, there were large changes in oxygen concentrations in this atmosphere, ranging from 15 to 35 per cent, having been determined by a combination of cosmic-climatic, tectonic-volcanic and biological phenomena. A particular environmental change occurred at the beginning of the 19th century, as a result of the overlap of the end of the natural Little Ice Age and the beginning of anthropogenic warming of the ‘industrial revolution’. According to the author, the rate of human impact on environmental changes is estimated at about 15 per cent. The appearance of mankind brought new changes in the natural environment, including the oxygen content of the air. The current scale of anthropogenic impact justifies the introduction of a new time slice in the planet’s history - the Anthropocene. The functioning of civilisation is conditioned by meeting energy needs, to be implemented by creating a system of energy generators, among which the heat of the Earth should be an important component. The energy generated from this inexhaustible and cost-free geo-resource should be seen as the most ecological among all currently used energy carriers.